CYBERCRIME CHALLENGES: EXPERIENCE OF INTERNATIONAL COOPERATION - Satbayeva Айжан Муратовна; Alimbetova Алида Робертиновна; Beissenbayeva Маншук Токтарбековна (Scientific and legal journal «Bulletin of the Institute of Legislation and Legal Information of the Republic of Kazakhstan», 2024)
The study focuses on the problem of countering cybercrime in the context of the experience of international cooperation. The trend in the process of ongoing transformation from a post-industrial to an information society stands out: global informatization and digitalization of processes lead to the threat of interference in personal life, data theft, and violation of privacy. The analysis of international legal acts made it possible to conclude the need to expand cooperation between states in the fight against cybercrime under the auspices of the UN based on programmatic, strategic acts of international legal regulation of the relevant range of relations. The importance of creating and developing organizational and legislative measures to combat cybercrime, improving interaction between the competent authorities of various states, as well as the need to develop and adopt universal conventions to combat cybercrime, is noted. The authors of the article state that the large-scale growth in the volume of information transfer causes the need to ensure the maximum level of data protection, both by the interested ICT users themselves and by governments - guarantors of state information security and stability. The international legal framework provides a solution to the problem in three areas: reducing discrepancies between national laws, introducing new powers of bodies, and promoting international cooperation. It is stated that in the Republic of Kazakhstan, there are no comprehensive studies on combating cyberterrorism and cybercrime as phenomena that include the entire range of crimes that are committed today on the Internet. The study fills this gap: the activities of the legislative and law enforcement bodies of the Republic of Kazakhstan are analyzed. The authors focus on such positive aspects as the creation of the Ministry of Internal Affairs of the Republic of Kazakhstan in April 2003 of the "K" department to intensify the fight against a wide range of crimes related to computer and Internet technologies, including cyberbullying, the production of counterfeit video discs, the dissemination of information that contributes to extremism, terrorism, cruelty, and violence. Chapter 7 of the Criminal Code of the Republic of Kazakhstan, devoted to criminal offenses in the field of informatization and communications, was subjected to scientific turnover; Cybersecurity Concept ("Cyber Shield of Kazakhstan"); a pilot project of 2023, which launched a special cyber police unit "Cyberpol Strike Task Force" to protect citizens and businesses of the country from cyber threats.